1, 2, 3, Action: Using Performance in Higher Education to Develop Teachers and Learners - Becker, Kelly Mancini (LEARNing Landscapes, 2020)
This paper explores the use of performance in a college-level course that teaches education majors how to use drama, dance, and music in their instruction. Students engage in drama activities such as improvisation and playbuilding in an effort to experience firsthand the benefits of such practices for their future classrooms. The essay shares some of the students’ experiences in this course. A common outcome shared is that the processes encouraged students to get out of their comfort zone, which they found beneficial to their learning. The essay examines how having students perform may help them develop as both a learner and a future teacher.